A NEW DIGITAL ART GAME: THE ART OF THE FUTURE - Gintere, Ieva (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The task of this study is to create an innovative digital art game of contemporary aesthetics on the basis of research. Research implies the analysis of digital art games and the historical background of their aesthetics, as well as their classification following the stylistic trends. Digital games have a great potential to integrate people into fields that would otherwise not meet their interest. The new game would develop the creative skills of players and teach them the current trends in digital art. The game would project the inheritance of art from the age of modernism into the digital world by teaching the player to recognize it (for instance, pixel aesthetics is a successor to cubism and constructivism). The new game will let its user play around with the trends in digital art such as vaporwave, glitch and others, and to create new ones. Thus, it would deal with the problem of knowledge cache and cultural segregation that characterizes modern art: being an esoteric subject to a great extent, it is difficult to access a large segment of the public. The aim of this study is to raise the interest of a wide-ranging public for contemporary art and to point out the newest creative tendencies in art. The paper presents an overview of digital art games, introduces a novel term, vaporwave, that has not been registered in the art game discourse so far, and offers an updated definition of the art game. The Design Science Research method is used in order to cross-cut such remote fields as the general public and the arthouse world, codes of modern art and the taste of the general public.